1993
DOI: 10.1111/j.1432-1033.1993.tb17857.x
|View full text |Cite
|
Sign up to set email alerts
|

Human 4‐hydroxyphenylpyruvate dioxygenase

Abstract: We report the primary structure of 4-hydroxyphenylpyruvate dioxygenase [4-hydroxyphenylpyruvate : oxygen oxidoreductase (hydroxylating, decarboxylating)]. The work is based on the isolation of cDNA clones from human liver Agtll libraries. Several overlapping clones covering the coding sequence were characterized. In parallel, peptides from four different digests of the purified protein were analysed for their amino-acid sequence. These peptide sequences covered 86% of the cDNA-derived amino-acid sequence. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
29
2

Year Published

1994
1994
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 53 publications
6
29
2
Order By: Relevance
“…The possible role of rat F antigen only came to light when 4HPPD from Streptomyces, human and porcine were cloned [16,18,19]. Sequence comparison showed that RFA bore a striking similarity to 4HPPD isolated from these organisms.…”
Section: Otkicd Activitymentioning
confidence: 99%
“…The possible role of rat F antigen only came to light when 4HPPD from Streptomyces, human and porcine were cloned [16,18,19]. Sequence comparison showed that RFA bore a striking similarity to 4HPPD isolated from these organisms.…”
Section: Otkicd Activitymentioning
confidence: 99%
“…Genes and cDNAs encoding HPPDase have been identified from several mammalian, fungal, bacterial, and plant sources (Gershwin et al, 1987;Endo et al, 1992Endo et al, , 1995Hummel et al, 1992;Ruetschi et al, 1993;Coon et al, 1994;Denoya et al, 1994;Wilson et al, 1994;Wintermeyer et al, 1994;Kaneko et al, 1995;Wyckoff et al, 1995;Garcia et al, 1997) and show between 25% and 95% identity at the amino acid level. A computer search of the plant DNA databases, including 20,000 random Arabidopsis cDNAs (Newman et al, 1994), was conducted using human and bacterial HPPDase sequences as the query.…”
Section: Isolation and Characterization Of An Arabidopsis Hppdase Cdnamentioning
confidence: 99%
“…In most organisms this enzyme activity is involved in the catabolism of the aromatic amino acid Tyr (Goodwin, 1972). All mammalian 4HPPDs purified so far behave as homodimers, with subunits of 43 to 49 kD (Wada et al, 1975;Lindblad et al, 1977;Roche et al, 1982;Endo et al, 1992;Rû etschi et al, 1993). In contrast, the Pseudomonas sp.…”
mentioning
confidence: 99%
“…This reaction proceeds through an oxidative decarboxylation of the 2-oxoacid side chain of the substrate, which is accompanied by hydroxylation of the aromatic ring and a 1,2-migration of the carboxymethyl group (Jefford and Cadby, 1981). The purified enzyme was shown to contain nonheme-reduced iron, which is essential for catalytic activity (Wada et al, 1975;Lindblad et al, 1977;Roche et al, 1982;Endo et al, 1992;Rû etschi et al, 1993). This enzyme belongs to the extradiol ␣-ketoaciddependent group of dioxygenases.…”
mentioning
confidence: 99%